Polyfluoroether functional group-containing additive and application thereof in battery

By using polyfluoroether functional group additives in sodium ion batteries, the composition of the electrolyte is optimized and a thin and dense SEI film is formed, which solves the problem of low efficiency of sodium ion batteries for the first time, and significantly improves the electrochemical performance and service life of the battery.

CN119518099APending Publication Date: 2025-02-25SUZHOU PUCHANG NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411730765.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing sodium ion batteries have low efficiency in the first week of the first electrochemical cycle, resulting in poor electrochemical performance and insufficient interface compatibility between the electrolyte and the hard carbon negative electrode.

Method used

By optimizing the proportion of HPP additives in the electrolyte, the viscosity, wetting and interface compatibility of the electrolyte are adjusted to form a thin and dense inorganic SEI film, and the effective utilization rate of sodium ions is improved.

Benefits of technology

It significantly improves the first Coulomb efficiency, discharge specific capacity and cycle stability of sodium ion batteries, improves the interface compatibility between the electrolyte and the hard carbon negative electrode, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005160205680000021
    Figure BDA0005160205680000021
  • Figure BDA0005160205680000081
    Figure BDA0005160205680000081
  • Figure FDA0005160205670000011
    Figure FDA0005160205670000011
Patent Text Reader

Abstract

The invention discloses an additive containing a polyfluoroether functional group and application of the additive in a battery, and relates to the technical field of sodium ion batteries. The method comprises the following steps: weighing electrolyte EC and electrolyte PC according to a mass ratio, completely and uniformly dissolving the electrolyte EC and the electrolyte PC, adding a sodium salt with the concentration of 0.8-1.2 M, and completely dissolving the sodium salt for later use; and respectively adding an additive A, an additive B and an additive C with different concentrations into the electrolyte to prepare the sodium-ion battery electrolyte. The sodium-ion battery electrolyte prepared by the preparation method can remarkably improve the first-circle coulombic efficiency, the specific discharge capacity and the cycle life, and is suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion batteries, in particular to an additive containing a polyfluoroether functional group and application thereof in batteries. Background Art

[0002] Sodium-ion batteries (SIBs) have attracted the attention of researchers due to their advantages such as high energy density, long life, environmental protection and low cost. The electrolyte plays an important role in sodium-ion batteries. It affects the electrochemical window, ion conduction rate, effective ion utilization and battery safety. As we all know, the low first coulomb efficiency has very serious consequences on the electrochemical performance of sodium-ion batteries. In other words, improving the effective utilization rate of the first sodium ions is one of the most intuitive evaluation methods to improve the discharge specific capacity. Therefore, it is urgent to explore an electrolyte with good compatibility with the hard carbon negative electrode, which can effectively improve the interface between the electrolyte and the hard carbon negative electrode, adjust the composition of the interface phase, and improve the electrochemical performance of the battery.

[0003] In the first electrochemical cycle of the battery, most of the first-cycle coulombic efficiency loss occurs during the formation of the solid electrolyte interface film (SEI) film. In most cases, no matter which method is used, the key to obtaining sufficient first-cycle coulombic efficiency is to design a thin and stable SEI film that can withstand multiple insertion and extraction processes of sodium ions. Therefore, strategies such as reducing the surface area, changing the electrolyte system, adding electrolyte additives, controlling the content of active functional groups, and surface coating are helpful to form a thinner SEI film and a higher first-cycle coulombic efficiency.

[0004] Electrolyte is one of the essential components of batteries. In practical applications, SIBs with different requirements can be assembled to meet battery performance by purposefully selecting battery components. Therefore, it is very important to explore an electrolyte that is compatible with hard carbon. Many studies have found that ether electrolytes have good electrochemical compatibility with hard carbon, a negative electrode material for sodium ion batteries, which can improve the initial Coulombic efficiency and rate capability of electrode materials and enhance electrochemical performance. In addition, fluorine-containing compounds have obvious advantages in physical properties, solvation structure, interface chemistry, interface transport, oxidation potential, high and low temperatures, current collector dissolution, safety and gas release.

[0005] First, fluorinated linear ethers with CF endcapping show higher viscosity and comparable solvation capacity than their non-fluorinated counterparts, while in the case of polyfluorinated and perfluorinated solvents, viscosity and salt solvation capacity are reduced. Therefore, polyfluorinated and perfluorinated solvents can serve as unique media to adjust the viscosity, wettability, flammability, and interfacial compatibility of electrolytes. Second, the strong electron-withdrawing property of fluorine atoms can affect the solvation capacity of solvents, and fluorinated solvents show lower Na+ than their non-fluorinated counterparts. +Solvation ability, its weak solvation ability can increase the anion content in the solvation sheath, thereby enhancing the Na + Third, fluorinated solvents can also enhance the properties of the interfacial layer. First, the degradation of fluorinated solvents will form an interfacial layer (SEI or CEI) rich in NaF or F-containing complexes, which provides high interfacial chemical and mechanical stability. Second, the unique Na in fluorinated solvents with low solvating power + -The anion solvation structure is also conducive to the formation of NaF, which helps to form a dense and well-passivated interface layer, allowing uniform ion flux and reducing interface resistance, but its poor ionic conductivity may reduce the ion transport capacity of the carbon-based negative electrode. Fourth, fluorination can reduce the ionic conductivity of the electrolyte. Balancing the bulk and interface transport is one of the most important issues in designing advanced fluorinated solvents. The position of fluorine and the distance from the characteristic functional groups of the molecule are highly correlated with the properties of the solvent and its formulated electrolyte. Therefore, the characteristics of ethers and polyfluorinated compounds are combined to achieve the improvement of the electrode / electrolyte interface phase, the adjustment of the components of the interface phase, and the improvement of the effective utilization rate of sodium ions and other shortcomings of sodium-ion batteries. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing an electrolyte additive, by optimizing the proportion of the HPP additive in the electrolyte, that is, adjusting the content of the additive, so as to improve the first coulombic efficiency and the electrochemical performance of the sodium ion battery.

[0007] The specific operation includes the following steps:

[0008] A polyfluoroether functional group-containing additive and its application in a battery, characterized in that the electrolyte comprises: sodium salt, electrolyte, additive A, additive B and additive C.

[0009] As a preferred technical solution of the present invention, the additive A is a compound of the structure shown in FIG. 12 O(HPP).

[0010]

[0011] As a preferred technical solution of the present invention, the preparation method of the additive B is:

[0012] By weight, 10-20 parts of 1,2-dimercapto-o-carborane, 2-5 parts of allyl polyoxyethylene ether, 0.02-0.5 parts of tributyl isopropenyl tin, 4-9 parts of triethylamine and 100-200 parts of methyl pyrrolidone are stirred and reacted at 70-80° C. for 40-100 minutes, and then 30-50 parts of perfluoropolyether (meth) acrylate are added, and the methyl pyrrolidone is distilled off to obtain additive B.

[0013] As a preferred technical solution of the present invention, the additive C is fluoroethylene carbonate (FEC), which accounts for 3-6wt% of the total mass of the electrolyte.

[0014] As a preferred technical solution of the present invention, the additive A and the additive B are 1-5wt% based on the total mass of the electrolyte.

[0015] As a preferred technical solution of the present invention, the sodium salt is sodium hexafluorophosphate (NaPF6) or sodium perchlorate (NaClO4).

[0016] As a preferred technical solution of the present invention, the electrolyte is a mixture of ethylene carbonate (EC) and propylene carbonate (PC) = 1:0.8-1.2, and the volume ratio is 1:1.

[0017] As a preferred technical solution of the present invention, the positive electrode of the sodium ion battery is a Na sheet.

[0018] As a preferred technical solution of the present invention, the negative electrode of the sodium ion battery is hard carbon (HC).

[0019] As a preferred technical solution of the present invention, the preparation method of the electrolyte is:

[0020] (1) Weigh the electrolyte EC and PC in a mass ratio of 1:1, and after the two liquids are completely and evenly dissolved, add sodium salt with a concentration of 0.8-1.2M, and set aside after the sodium salt is completely dissolved;

[0021] (2) Adding different concentrations of additive A, additive B and additive C to the electrolyte in step (1) to prepare a sodium ion battery electrolyte.

[0022] The present invention provides a sodium ion battery electrolyte with improved first-cycle coulombic efficiency, which is prepared by the above-mentioned preparation method.

[0023] Among them, the preparation mechanism of additive B is:

[0024] 1,2-dimercapto-o-carborane is subjected to mercapto-ene addition reaction with allyl polyoxyethylene ether and tributyl isopropenyltin, and then to mercapto-ene addition reaction with perfluoropolyether (meth)acrylate to obtain a perfluoropolyether compound containing carborane, tin complex and polyoxyethylene ether, which is used as an additive in sodium ion electrolyte.

[0025] The thiol (-SH) in 1,2-dithiol-o-carborane undergoes a thiol-ene addition reaction with the alkenyl in allyl polyoxyethylene ether to form a thioether bond.

[0026] Another mercapto group in the above reaction product undergoes a mercapto-ene addition reaction with the olefinic group in tributyltin isopropenyl to further form a tin-containing sulfide bond.

[0027] The intermediate containing carborane and tin obtained by the first two steps of reaction undergoes a mercapto-ene addition reaction with the olefinic group in the perfluoropolyether (meth)acrylate, and finally obtains a perfluoropolyether compound containing carborane, a tin complex and polyoxyethylene ether.

[0028] The above-mentioned additive B has the following effects:

[0029] 1. Improve the stability of the electrolyte:

[0030] Perfluoropolyether compounds containing carborane, tin complex and polyoxyethylene ether may improve the thermal stability and chemical stability of the electrolyte through their unique chemical structure and reduce the decomposition of the electrolyte under high temperature or harsh conditions.

[0031] 2. Enhance the conductivity of the electrolyte:

[0032] The perfluoropolyether group may help improve the ionic conductivity of the electrolyte because the perfluoropolyether structure can provide low viscosity and good ion solubility.

[0033] 3. Improve battery performance:

[0034] Electrolytes using this additive may help improve the charge and discharge efficiency and cycle stability of sodium-ion batteries, thereby extending the battery life.

[0035] 4. Reduce the corrosiveness of the electrolyte:

[0036] The introduction of perfluoropolyether compounds may reduce the corrosive effect of electrolyte on battery components, especially under high voltage conditions.

[0037] Technical mechanism of the above scheme:

[0038] The present invention provides a method for adjusting the electrolyte and hard carbon negative electrode interface phase to improve the first coulombic efficiency of sodium ion batteries. First, COC in the HPP molecule is an ether functional group, and the diffusion coefficient of sodium ions in ether electrolytes is about 2.5 times higher than that in ester electrolytes. When the solvated sodium ions diffuse to the SEI interface and the interior of the hard carbon material, the enhanced charge transfer kinetics (thin SEI layer and low RSEI) and the low desolvation energy at the SEI interface give the hard carbon material high rate performance and good cycle stability in ether electrolytes. Secondly, the CF in the HPP can form NaF-rich or F-containing inorganic compounds at the electrode / electrolyte interface, thereby providing high interfacial chemical and mechanical stability. In addition, the polyfluorinated solvent HPP molecule reduces the viscosity and the ability to dissolve salts. Therefore, polyfluorinated and perfluorinated solvents can be used as unique media to adjust the viscosity, wettability, flammability and interfacial compatibility of the electrolyte. Therefore, high diffusion coefficient, low desolvation energy and good interface are the intrinsic reasons for the improvement of effective sodium ion in polyfluorinated ether-based electrolytes, which can also provide certain guidance for the design of other electrolytes.

[0039] Technical effect:

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] (1) The present invention provides a preparation method for improving discharge capacity, which improves the coulombic efficiency of the sodium ion battery during the first charge and discharge process by optimizing the proportion of HPP additives in the electrolyte, and adjusts the interface phase between the electrolyte and the hard carbon negative electrode, that is, using ether-based solvents and NaPF6 salts to form a thin and dense inorganic SEI film on the surface of metallic sodium, increasing Na2O and NaF in the SEI film, and effectively inhibiting the growth of sodium dendrites. Thereby improving the compatibility between the electrolyte and the hard carbon negative electrode, and ultimately improving the discharge specific capacity and cycle stability of the sodium ion battery.

[0042] (2) The preparation process provided by the present invention is relatively simple, the dosage is small, and the overall performance of the sodium ion battery is improved with a small amount of additives. It is suitable for large-scale industrial production; the product performance is relatively good and has certain competitive advantages. DETAILED DESCRIPTION

[0043] The present invention will be further described below in conjunction with specific embodiments. The following embodiments are only used to illustrate the present invention and are not intended to limit the scope of application of the present invention. Without departing from the spirit and essence of the present invention, modifications or replacements made to the inventive method, steps or conditions all belong to the scope of the present invention.

[0044] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.

[0045] Example 1

[0046] This embodiment provides a preparation method for improving discharge specific capacity and first coulombic efficiency, comprising the following components:

[0047] 50% Ethylene carbonate (EC) solvent

[0048] 50% Propylene Carbonate (PC) Solvent

[0049] 5% Fluoropropylene carbonate (FEC) additive

[0050] 1M NaPF6

[0051] This embodiment also provides a method for preparing a sodium ion electrolyte for improving the first coulombic efficiency and adjusting the SEI film components. The method comprises the following steps: in a glove box at room temperature, the electrolyte solvent is uniformly mixed according to the mass ratio, and then sodium hexafluorophosphate is dissolved in the mixed electrolyte solvent. The mixture is uniformly mixed.

[0052] Example 2

[0053] This embodiment provides a preparation method for improving discharge specific capacity and first coulombic efficiency, comprising the following components:

[0054] 50% Ethylene carbonate (EC) solvent

[0055] 50% Propylene Carbonate (PC) Solvent

[0056] 5% Fluoropropylene carbonate (FEC) additive

[0057] 1M NaPF6

[0058] 1% Perfluoropolyether C5F 12 O(HPP)

[0059] 0.2% additive B, the preparation method of additive B:

[0060] 10 g of 1,2-dimercapto-o-carborane, 2 g of allyl polyoxyethylene ether, 0.02 g of tributyl isopropenyltin, 4 g of triethylamine and 100 g of methyl pyrrolidone were stirred and reacted at 70° C. for 40 min, and then 30 g of perfluoropolyether (meth) acrylate was added. The methyl pyrrolidone was distilled off to obtain additive B.

[0061] This embodiment also provides a method for preparing a sodium ion electrolyte for improving the first coulombic efficiency and adjusting the SEI film components. The method comprises the following steps: in a glove box at room temperature, the electrolyte solvent and the additive are uniformly mixed according to a mass ratio, and then sodium hexafluorophosphate is dissolved in the mixed electrolyte solvent. The mixture is uniformly mixed.

[0062] Example 3

[0063] This embodiment provides a preparation method for improving discharge specific capacity and first coulombic efficiency, comprising the following components:

[0064] 50% Ethylene carbonate (EC) solvent

[0065] 50% Propylene Carbonate (PC) Solvent

[0066] 5% Fluoropropylene carbonate (FEC) additive

[0067] 1M NaPF6

[0068] 2% Perfluoropolyether C5F 12 O(HPP)

[0069] 0.5% additive B, the preparation method of additive B:

[0070] 15 g of 1,2-dimercapto-o-carborane, 3.5 g of allyl polyoxyethylene ether, 0.2 g of tributyl isopropenyltin, 5.5 g of triethylamine and 150 g of methyl pyrrolidone were stirred at 75°C for 60 min, 40 g of perfluoropolyether (meth) acrylate was added, and the methyl pyrrolidone was distilled off to obtain additive B.

[0071] This embodiment also provides a method for preparing a sodium ion electrolyte for improving the first coulombic efficiency and adjusting the SEI film components. The method comprises the following steps: in a glove box at room temperature, the electrolyte solvent and the additive are uniformly mixed according to a mass ratio, and then sodium hexafluorophosphate is dissolved in the mixed electrolyte solvent. The mixture is uniformly mixed.

[0072] Example 4

[0073] This embodiment provides a preparation method for improving discharge specific capacity and first coulombic efficiency, comprising the following components:

[0074] 50% Ethylene carbonate (EC) solvent

[0075] 50% Propylene Carbonate (PC) Solvent

[0076] 5% Fluoropropylene carbonate (FEC) additive

[0077] 1M NaPF6

[0078] 3% Perfluoropolyether C5F 12 O(HPP)

[0079] 0.8% additive B, the preparation method of additive B:

[0080] 15 g of 1,2-dimercapto-o-carborane, 4 g of allyl polyoxyethylene ether, 0.4 g of tributyl isopropenyltin, 8 g of triethylamine and 150 g of methyl pyrrolidone were stirred at 75° C. for 80 min, and 40 g of perfluoropolyether (meth) acrylate was added. The methyl pyrrolidone was removed by distillation to obtain additive B.

[0081] This embodiment also provides a method for preparing a sodium ion electrolyte for improving the first coulombic efficiency and adjusting the SEI film components. The method comprises the following steps: in a glove box at room temperature, the electrolyte solvent and the additive are uniformly mixed according to a mass ratio, and then sodium hexafluorophosphate is dissolved in the mixed electrolyte solvent. The mixture is uniformly mixed.

[0082] Example 5

[0083] This embodiment provides a preparation method for improving discharge specific capacity and first coulombic efficiency.

[0084] The method comprises the following components:

[0085] 50% Ethylene carbonate (EC) solvent

[0086] 50% Propylene Carbonate (PC) Solvent

[0087] 5% Fluoropropylene carbonate (FEC) additive

[0088] 1M NaPF6

[0089] 5% Perfluoropolyether C5F 12 O(HPP)

[0090] 1% additive B, the preparation method of additive B:

[0091] 20 g of 1,2-dimercapto-o-carborane, 5 g of allyl polyoxyethylene ether, 0.5 g of tributyl isopropenyltin, 9 g of triethylamine and 200 g of methyl pyrrolidone were stirred and reacted at 80° C. for 100 min, and then 50 g of perfluoropolyether (meth) acrylate was added. The methyl pyrrolidone was distilled off to obtain additive B.

[0092] This embodiment also provides a method for preparing a sodium ion electrolyte for improving the first coulombic efficiency and adjusting the SEI film components. The method comprises the following steps: in a glove box at room temperature, the electrolyte solvent and the additive are uniformly mixed according to a mass ratio, and then sodium hexafluorophosphate is dissolved in the mixed electrolyte solvent. The mixture is uniformly mixed.

[0093] Test Example 1: Electrochemical Performance Test

[0094] Battery assembly: The hard carbon negative electrode materials obtained in Examples 1 to 5 were used as active materials, respectively, and mixed according to the mass ratio of active material: ultrafine carbon powder (SP): polyvinylidene fluoride of 90:5:5, and N-methylpyrrolidone (NMP) was added to make a viscous glue, which was coated on aluminum foil and baked in a vacuum drying oven at 120°C for 12h to obtain a negative electrode sheet. A 2032 button-type sodium ion battery was assembled in an Ar gas protection glove box using a metal sodium sheet as a counter electrode, glass fiber (Waterman) as a diaphragm, and 1mol / LNaPF6 (EC and PC with a solvent mass ratio of 1:1) as an electrolyte. The Na-HC half-cell was tested in the voltage range of 0 to 2.0V, first discharged at a rate of 0.1C, then discharged at 0.01C to a voltage of 0V, and then charged at 0.1C to 2.0V.

[0095] Test results;

[0096]

[0097] The above test results fully demonstrate the technical effect. The additives of this method significantly improve the coulombic efficiency, discharge specific capacity and cycle life in sodium ion batteries, and are suitable for large-scale industrial production.

[0098] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A polyfluoroether functional group-containing additive and its application in a battery, characterized in that: The electrolyte comprises: sodium salt, electrolyte, additive A, additive B and additive C.

2. The polyfluoroether functional group-containing additive and its use in a battery according to claim 1, characterized in that: The additive A is a compound of the structure shown in FIG. 12 O(HPP).

3. The polyfluoroether functional group-containing additive and its use in a battery according to claim 1, characterized in that: Preparation method of the additive B: By weight, 10-20 parts of 1,2-dimercapto-o-carborane, 2-5 parts of allyl polyoxyethylene ether, 0.02-0.5 parts of tributyl isopropenyl tin, 4-9 parts of triethylamine and 100-200 parts of methyl pyrrolidone are stirred and reacted at 70-80° C. for 40-100 minutes, and then 30-50 parts of perfluoropolyether (meth) acrylate are added, and the methyl pyrrolidone is distilled off to obtain additive B.

4. The polyfluoroether functional group-containing additive and its use in a battery according to claim 1, characterized in that: The additive C is fluoroethylene carbonate (FEC), and the ester thereof accounts for 3-6% of the total mass of the electrolyte.

5. The polyfluoroether functional group-containing additive and its use in a battery according to claim 1, characterized in that: The additive A and the additive B are 1-5 wt % based on the total mass of the electrolyte.

6. The polyfluoroether functional group-containing additive and its use in a battery according to claim 1, characterized in that: The sodium salt is sodium hexafluorophosphate (NaPF6) or sodium perchlorate (NaClO4).

7. The polyfluoroether functional group-containing additive and its use in a battery according to claim 1, characterized in that: The electrolyte is a mixture of ethylene carbonate (EC) and propylene carbonate (PC) = 1:0.8-1.2, and the volume ratio is 1:

1.

8. The polyfluoroether functional group-containing additive and its use in a battery according to claims 1-7, characterized in that: The preparation method of the electrolyte: (1) Weigh the electrolyte EC and PC in a mass ratio of 1:1, and after the two liquids are completely and evenly dissolved, add sodium salt with a concentration of 0.8-1.2M, and set aside after the sodium salt is completely dissolved; (2) Adding different concentrations of additive A, additive B and additive C to the electrolyte in step (1) to prepare a sodium ion battery electrolyte.